2014
DOI: 10.4028/www.scientific.net/amr.1010-1012.1104
|View full text |Cite
|
Sign up to set email alerts
|

Factors to Affect the Eutrophication and Phytoplankton Blooms in the Three Gorges Reservoir

Abstract: The phytoplankton blooms in the tributary bays have become the most serious environmental problem in Three Gorge Reservoir (TGR), China. In order to understand the mechanism of those phytoplankton blooms, the factors to affect the eutrophication and Phytoplankton blooms have been summarized. Generally, in lakes eutrophication is a natural evolutionary process, which is affected by light, temperature, nutrients, predation, migration and stratification. Recent decade's human activities played a role to promote t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Since the impoundment of the TGR, algal blooms have occurred frequently in tributary bays (Stone, 2008;Yang et al, 2022). Accordingly, the dominant species of algal blooms in key tributaries evolved from channel-type algae dominated by Bacillariophyta and dinoflagellates in the early stage of impoundment to lake-type algae dominated by cyanobacteria and Chlorophyta (Liu et al, 2016;Yang et al, 2017;Yao et al, 2022). On the other hand, by comparing the results from different studies on the monitoring of DO in some tributary bays, we found that there was a clear decreasing trend of DO concentration in the water of the tributary bays of TGR in recent years.…”
Section: The Vicious Cycle Among Hypoxia Algal Blooms and Ch 4 /Co 2 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the impoundment of the TGR, algal blooms have occurred frequently in tributary bays (Stone, 2008;Yang et al, 2022). Accordingly, the dominant species of algal blooms in key tributaries evolved from channel-type algae dominated by Bacillariophyta and dinoflagellates in the early stage of impoundment to lake-type algae dominated by cyanobacteria and Chlorophyta (Liu et al, 2016;Yang et al, 2017;Yao et al, 2022). On the other hand, by comparing the results from different studies on the monitoring of DO in some tributary bays, we found that there was a clear decreasing trend of DO concentration in the water of the tributary bays of TGR in recent years.…”
Section: The Vicious Cycle Among Hypoxia Algal Blooms and Ch 4 /Co 2 ...mentioning
confidence: 99%
“…The TGR, as China's largest strategic freshwater resource reservoir, has been the focus of many scholars studying water quality and algal blooms in its tributary bays after its impoundment (Liu et al, 2016;Yang et al, 2017;Yang et al, 2022). Previous monitoring results (Zhang et al, 2009) show that the DO concentration in the TGR is generally higher than 6 mg•L -1 , and there have been no occurrences of hypoxic or anaerobic conditions in the waters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation